Postcranial skeleton of Postosuchus kirkpatricki (Archosauria: Paracrocodylomorpha), from the upper Triassic of the United States - Weinbaum, Jonathan C (Geological Society, London, Special Publications, 2013)
Postosuchus kirkpatricki is a Late Triassic (Norian) 'rauisuchid' archosaur from North America. The initial description of the Postosuchus type material included elements from two poposaurids. This confusion has prevented adequate description of the material. Recent examination of the type material and other specimens of Postosuchus, and of related taxa, has helped clarify the osteology of Postosuchus. The type specimens represent c. 75% of the skeleton. Together with other referred material, Postosuchus remains one of the most completely known rauisuchids. The paratype skeleton, which is relatively complete, would have been c. 3.5-4 m in length, and the holotype would have been closer to 5-6 m. Analysis of the postcranial skeleton of Postosuchus suggests that it may have been an obligate biped (based in part on limb proportions, which are similar to some theropod dinosaurs, the size of the manus (30% of the size of the pes) and the highly reduced nature of the digits and vertebral measurements). Possible postcranial autapomorphies of Postosuchus include a large, rugose triangular supra-acetabular buttress confluent with the dorsal margin of the iliac blade, and a symmetrical pes with digits two and three being roughly equal in length. © The Geological Society of London 2013.
Keywords: Triassic; United States; dept.bio; osteology; peer-reviewed; reptile; skeleton; taxonomy; type specimen

A survey of skeletal elements in the orbit of Pseudosuchia and the origin of the crocodylian palpebral - Nesbitt, Sterling J.; Turner, Alan H.; Weinbaum, Jonathan C. (Earth and Environmental Science Transactions of The Royal Society of Edinburgh, 2012)
Keywords: Aetosaurus ferratus; Archosauria; Crocodylomorpha; Postosuchus kirkpatricki; Saurosuchus galilei; crocodilian; dept.bio; evolution; extinction; fossil assemblage; novelty; skeletal remains; supraorbital; taxonomy